KONTROL SIRKULASI IKLIM DAN TEKTONIK TERHADAP ENDAPAN SEDIMEN SUNGAI PURBA BERUMUR PLISTOSEN DI DESA MULYASEJATI, KARAWANG DAN CILANGKAP, PURWAKARTA - Moechtar, H.; Subiyanto, Subiyanto (Pusat Survei Geologi, 2011)
A study on the conglomeratic sandstone and siltstone unit (Qoa) in the Mulyasejati Village (Kabupaten Karawang) and Conglomeratic and tuffaceous sandstone unit (Qav) of Pleistocene age in the Cilangkap Village (Kabupaten Purwakarta) has been carried out. The objectives of this paper are to reconstruct the mechanism of Depositional Period Intervals (DPI) of each lithologic unit. Sedimentological and stratigraphical analyses were carried out in the field based on seven vertical measured section of 1:50 scales. The thickness of the sections range from 1.20 to 7.70 m. Based on the correlation, both of lithostratigraphic units belong to into fluvial systems, and can be divided into four DPI (A to D). The sedimentary facies pattern of each DPI is controlled by the thrust structure, and are shown by stacking channels (FAS) 1 to 4. Whereas, the vertical composition of sediment is controlled by the fluctuation humidity related to climate change following Milankovitch cycles. Changes in the colour and composition of the sediments of the fluvial systems during the depositional processes of DPI A-D, can be interpereted as the result of climate changes. The climate circulations starting from nearly climatic optimum to climatic minimum or even dry.Keywords: facies, fluvial, climate, Interval of Deposition Periods